The visualization multimedia design model - a new approach to developing personalized mental training technological tools to enhance elite athlete performance - Chisamore, C.; Katz, L.; Paskevich, D.; Kopp, G. (International Journal of Computer Science in Sport, 2004)
Providing an athlete with the mental tools necessary to build, maintain or regain confidence can aid the athlete in achieving peak, or optimal performance. Many of the procedures and practices in mental training involve technology. This technology, ranges from digital video and audiotapes, to simulations and virtual reality. In this article the authors review the areas of sport efficacy and sport technology as they relate to athlete performance. The Visualization Multimedia Design Model (VMDM) is then introduced as a theoretical base for designing personalized technological mental training tools. These tools can be used by elite level athletes to help them mentally prepare for competition and peak athletic performance.